JLK1486, a N,N‐[(8‐hydroxyquinoline)methyl]‐substituted benzylamine analogue, inhibits melanoma proliferation and induces autophagy - Koekemoer, T. C. (Cell Prolif, 2014)
OBJECTIVES: To investigate anti‐proliferatory activity of a selected N,N‐[(8‐hydroxyquinoline)methyl]‐substituted benzylamine (JLK1486) on melanoma cells and to characterize its mechanism of cell population growth inhibition. MATERIALS AND METHODS: In vitro cultures of B16F10 (mouse melanoma) cells were used as a model to characterize anti‐proliferatory activity of JLK1486 using MTT growth assay, trypan blue viability assessment, cell cycle analysis, melanin production, β‐galactosidase and acridine orange staining. RESULTS: Proliferating B16F10 and also MeWo (human melanoma) cells were strongly growth inhibited by JLK1486, displaying IC (50) values of 196 nm and 110 nm respectively. Anti‐proliferatory effects were independent of cell death and were characterized by a distinct accumulation of cells in G(0)/G(1) phase. Tyrosinase activity and relative melanin content remained unchanged indicating that the anti‐proliferatory activity was not due to phenotype differentiation. Although treated B16F10 cells stained strongly positive for senescence marker β‐galactosidase, cells regained near normal proliferatory activity after removal of JLK1486. Increased acridine orange staining and presence of perinuclear vacuoles suggested induction of autophagy in B16F10 cells. Furthermore, JLK1486 pre‐treatment completely abolished melphalan and antimycin A‐induced apoptosis. CONCLUSION: JLK1486 provides a promising chemical scaffold to develop new anti‐melanoma drugs or combination therapies, due to its potent inhibition of cell proliferation and induction of autophagy, at pharmacologically relevant concentrations.